Prognostic factors and primary treatment for Waldenström macroglobulinemia – a Swedish Lymphoma Registry study - Brandefors, Lena; Melin, Beatrice; Lindh, Jack; Lundqvist, Kristina; Kimby, Eva (British journal of haematology, 2018)
We present a nationwide prospective Swedish registry‐based study of Waldenström macroglobulinaemia (WM), that focuses on incidence and survival in relation to clinical prognostic factors and primary systemic therapies. A total of 1511 patients with WM and lymphoplasmocytic lymphoma (LPL) were registered in the Swedish Lymphoma Registry (SLR) between 1 January 2000 and 31 December 2014. The age‐adjusted incidence of WM/LPL was 11·5 per million persons per year, three times higher than the reported incidence worldwide. Medical records were retrieved for 1135 patients (75%). A retrospective review showed that 981 (86·1%) of these patients fulfilled the World Health Organization diagnostic criteria for WM and these patients were analysed further. The overall survival (OS) improved between two periods – 2000–2006 and 2007–2014 – with a five‐year OS of 61% and 70%, respectively. Significant prognostic factors for OS, evaluated at the time of diagnosis, were age, elevated lactate dehydrogenase level and haemoglobin ≤115 g/l for patients receiving therapy 0–3 months after diagnosis, and age, poor performance status, haemoglobin ≤115 g/l, and female sex in “watch and wait” patients (multivariable analysis). The level of the IgM monoclonal immunoglobulin had no significant prognostic value. Rituximab included in first‐line therapy was associated with improved survival.